2002
DOI: 10.1046/j.1475-1313.2002.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between vision impairment and ability to perform activities of daily living

Abstract: Clinical vision impairment measures are highly correlated with capacity to perform ADLs, as measured by the MLVAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
133
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(141 citation statements)
references
References 51 publications
5
133
0
3
Order By: Relevance
“…82 There is considerable evidence that adults who are visually impaired have a poorer functional status in terms of ability to carry out both ADLs and IADLs than their fully sighted counterparts. 18,19,35,67,83,90,159 Lamoureux et al, for example, investigated the limitations in ADLs in 319 participants with a visual impairment with no visual rehabilitation history and found that reading, outdoor mobility, participation in leisure activities, and shopping were most limited. 90 Restricted mobility and orientation skills in individuals with visual impairment also make them more vulnerable to falls and associated complications such as hip fractures.…”
Section: A Consequences Of Visual Impairmentmentioning
confidence: 99%
“…82 There is considerable evidence that adults who are visually impaired have a poorer functional status in terms of ability to carry out both ADLs and IADLs than their fully sighted counterparts. 18,19,35,67,83,90,159 Lamoureux et al, for example, investigated the limitations in ADLs in 319 participants with a visual impairment with no visual rehabilitation history and found that reading, outdoor mobility, participation in leisure activities, and shopping were most limited. 90 Restricted mobility and orientation skills in individuals with visual impairment also make them more vulnerable to falls and associated complications such as hip fractures.…”
Section: A Consequences Of Visual Impairmentmentioning
confidence: 99%
“…[1][2][3][4][5][6] The severity of these mental/physical disorders is reportedly correlated with visual impairment.…”
Section: Introductionmentioning
confidence: 99%
“…More recently there is a coming up of trend in developing a method for evaluation of functional vision-performance-based measures (PBMs) of visual function. [13][14][15][16][17][18][19][20][21][22][23] It involves presenting patients with commonly encountered tasks of daily life in a standardized format and getting a grade in accordance with their visual ability to complete the tasks. Pioneering studies has demonstrated that PBMs can be reliable and valid methods in assessing real-life visual ability.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering studies has demonstrated that PBMs can be reliable and valid methods in assessing real-life visual ability. [13][14][15][16][17][18][19][20][21][22][23] Owing to its significance in visual hierarchy, PBMs of visual function is becoming an important part of researches on the real-life effects of visual diseases.…”
Section: Introductionmentioning
confidence: 99%